Changes in Arctic Stratification and Mixed Layer Depth Cycle: A Modeling Analysis. Issue 1 (21st January 2022) - Hordoir, Robinson; Skagseth, Øystein; Ingvaldsen, Randi B.; Sandø, Anne Britt; Löptien, Ulrike; Dietze, Heiner; Gierisch, Andrea M. U.; Assmann, Karen M.; Lundesgaard, Øyvind; Lind, Sigrid
Abstract: Climate change is especially strong in the region of the Arctic Ocean, and will have an important impact on its thermo‐haline structure. We analyze the results of a hindcast simulation of a new 3D ocean model of the Arctic and North Atlantic oceans for the period 1970–2019. We compared the time period 1970–1999 with the time period 2010–2019. The comparison showed that there is a decrease of stratification between the two periods over most of the shallow Arctic shelf seas and in the core of the Transpolar Ice Drift. Fresh water inputs to the ocean surface decline, and inputs of momentum to the ocean increase, which can explain the decrease in stratification. The comparison also showed that the mixed layer becomes deeper during winter, in response to the weakened stratification owing to increased vertical mixing. The comparison of summer mixed layer depths between the two time periods follows a deepening pattern that is less evident. Regional exceptions include the Nansen Basin and the part of the Canadian Basin bordering the Canadian Archipelago, where the mixed layer shoals. Trends of freshwater fluxes imply that the changes of haline stratification in these regions are also influenced by other processes, for example, horizontal advection of fresh water, increased mixing and changes in the underlaying water masses. Runoff increase toward the Arctic Ocean can locally decrease but also increase salinity, and has an impact on stratification which can be explained by coastal dynamics. The results emphasize the non‐linear nature of Arctic Ocean dynamics. Plain Language Summary: We analyzed the results of an ocean model simulation for the Arctic and North Atlantic oceans for the period 1970–2019. Our model is in line with the recent observed changes in the Arctic Ocean and allows, in contrast to the rather sparse observations, a detailed assessment of stratification changes. These changes will affect the Arctic ecosystem and are also believed to affect the large scale ocean circulation. We show that major changes in upper ocean conditions are caused by changes in the fresh water supply by sea ice and varying effect of the wind on regions that are now becoming ice‐free. We also study the effect of changes in river runoff into the Arctic Ocean. Our study shows that an increase in river runoff can change the coastal circulation and results, paradoxically, in regions of higher salinity. These results point to the importance of modeling tools when it comes to a better understanding of ocean processes in a changing climate. Key Points: Results from a hindcast simulation of the Arctic Ocean for the period 1970–2019 show strong changes in stratification The changes in stratification are explained by altered surface stress and freshwater fluxes Trends in river runoff have little effect on the mixed layer depth but change the Arctic coastal circulation